Ecological Legal Politics in Indonesia: The Critique within Muhammadiyah’s Fiqh during the Reformation Era - Wahdini, Muhammad; Jubba, Hasse; Kamsi, Kamsi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
The reform era witnessed a shift in the Tarjih Muhammadiyah Council’s legal outputs from monodisciplinary to multidisciplinary, resulting in a product known as responsive fiqh. Ecological political issues in Indonesia became a primary focus of this new approach. This research aims to analyze the Tarjih Muhammadiyah Council’s conceptual shift from monodisciplinary to multidisciplinary fiqh, and to explore how its critical fiqh responds to the ecological legal-political constellation in Indonesia during the reform era. This research employed normative legal research methods, utilizing a political approach to law. Data were gathered through literature review. The findings reveal that Muhammadiyah’s fiqh represents a new paradigm of responsive fiqh, aligned with the principles of tajdid and ijtihad. The shift in the Tarjih Council’s legal outputs is largely attributed to the leadership of its chairman. From the Tarjih Council’s diverse fiqh outputs, this research selected and highlighted Muhammadiyah’s fiqh products pertaining to ecology. First, the Fiqh of Water addresses the alarming, global water crisis, serving as the legal basis for Muhammadiyah’s judicial review of Law No. 7/2004 concerning Water Resources, which the Constitutional Court upheld, signifying the incorporation of this fiqh into Indonesia’s ecological political landscape. Second, the Fiqh of Disaster Management, addressing socio-community issues linked with ecological problems in disaster contexts, has not resulted in contestation or accommodation within ecological politics. Third, Agrarian Fiqh addresses varied agrarian challenges in Indonesia, including food self-sufficiency, environmental degradation, agrarian conflicts, indigenous community rights, and housing and public space access, thereby engaging in contestation with state policies within the realm of ecological politics. In this way, Muhammadiyah’s fiqh seeks to actively contribute to establishing a democratic political configuration by ensuring comprehensive and egalitarian influence on government policies.